Penerapan Hukum Program Jaminan Kesehatan Nasional (JKN) Terhadap Pelayanan Spesialis Akupuntur Medik Di Rumah Sakit Umum Daerah (RSUD) Kayuagung - Edi Suhaimi (Lex Stricta : Jurnal Ilmu Hukum, 2024)
This study examines the legal status of medical acupuncture services within the National Health Insurance (JKN) program, particularly following the termination of coverage by BPJS in January 2015 on the grounds that acupuncture was categorized as traditional health services under Presidential Regulation No. 12 of 2013 Article 25 (j). Previously, such services had been covered by PT. Askes under Joint Regulation No. 138/2009 of the Minister of Health and the Minister of Home Affairs. Using an empirical legal approach combined with statutory analysis, this research finds that there are two distinct regulatory frameworks: traditional acupuncture, performed by non-medical practitioners, and medical acupuncture, performed by certified physicians or specialists. Medical acupuncture in hospitals constitutes medical practice, encompassing examination, diagnosis, treatment, and specialized non-surgical interventions, as affirmed in Presidential Regulation No. 82 of 2018 Article 47 and supported by Minister of Health Regulation No. 28 of 2014. The study concludes that, based on the principle of lex specialis derogat legi generali, Presidential Regulation No. 82 of 2018 provides a legal foundation for including medical acupuncture services under JKN coverage.